Utilization of amorphous phase forming trityl groups and Ar-ArF interactions in synthesis of NLO active azochromophores. (August 2022) - Laipniece, Lauma; Kampars, Valdis; Belyakov, Sergey; Bundulis, Arturs; Tokmakovs, Andrejs; Rutkis, Martins
Abstract: New NLO active organic molecular glasses were synthesized based on push-pull azobenzene, which was dendronized with 3, 5-bis[2-(trityloxy)ethoxy]benzoic acid and pentafluorophenyl groups were added to enchance thermal and NLO properties via Ar-Ar F interactions. The configuration, where pentafluorophenyl groups containing dendronizing fragment was attached to donor part of azochromophore, was very promising in our recent research, therefore trityl groups containing dendron was added to acceptor part to rise the glass transition temperature of amorphous compound. Effect of one or two pentafluorophenyl groups was investigated and about three times better NLO parameters were obtained when using one pentafluorophenyl group, as it has greater possibility of NLO properties enchanting Ar-Ar F interactions with neighboring molecules. New convergent method was used to synthesize azobenzene core dendrimer fully functionalized with trityl end groups. Thermal, optical, and NLO properties were compared to previously reported results of dendrimer samples containing both hydroxyl and trityl groups. Full set of trityl end groups resulted in decreased NLO parameters and stability of poled order. Glass transition temperatures of all synthesized molecular glasses were 63–83 °C, and thermal destruction temperatures of all synthesized compounds were at least 250 °C. NLO coefficient d33 values were 14–73 pm⋅V −1 . Graphical abstract: Image 1 Highlights: Molecular glasses of pure compounds have high polar order of poled films. C6 F5 CH2 ether to alkyl fragment is synthesized in mild phase transfer catalysis. Azobenzene with one C6 F5 CH2 group and trityl dendron shows good NLO properties.